2016
DOI: 10.1093/nar/gkw933
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of the 70S ribosome from human pathogenStaphylococcus aureus

Abstract: Comparative structural studies of ribosomes from various organisms keep offering exciting insights on how species-specific or environment-related structural features of ribosomes may impact translation specificity and its regulation. Although the importance of such features may be less obvious within more closely related organisms, their existence could account for vital yet species-specific mechanisms of translation regulation that would involve stalling, cell survival and antibiotic resistance. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 104 publications
0
19
0
Order By: Relevance
“…Taken together, our data suggest that C-HPF SA forms the binding platform for the adjacent 30S, which is essential for S. aureus 100S dimerization. Furthermore, the superposition of our structure and the native SA70S 19 revealed that the presence of HPF SA induces a conformational change of helices h26 and h40 (Fig. 3d ).…”
Section: Resultsmentioning
confidence: 79%
“…Taken together, our data suggest that C-HPF SA forms the binding platform for the adjacent 30S, which is essential for S. aureus 100S dimerization. Furthermore, the superposition of our structure and the native SA70S 19 revealed that the presence of HPF SA induces a conformational change of helices h26 and h40 (Fig. 3d ).…”
Section: Resultsmentioning
confidence: 79%
“…Interestingly, a rod-like density, which is absent from other known prokaryotic ribosomes such as the EC 70S (Pulk and Cate, 2013 ), T . thermophilus 70S ( TT 70S) (Selmer et al, 2006 ), and Staphylococcus aureus 70S ( SA 70S) (Khusainov et al, 2016 ), locates in a pocket formed by h27, h44, and h45 close to the decoding center (DC) in the 30S subunit (Figs. 1 B, 1 D and S5E).…”
Section: Dear Editormentioning
confidence: 99%
“…An NAD captureSeq variant was also used to compare the enrichment of specific RNAs between S. aureus strains [pCG-P2, pCG-P3, and pCG-P3(Ϫ1G)]. For that, 15 fmol of NAD-RNAs of various lengths (61,104,205,302, and 400 nt) was spiked into each sample, acting as an internal standard (IS). The PCR products were purified by polyacrylamide (PA) gel electrophoresis (PAGE), and a range between 150 and 300 bp was selected (Fig.…”
Section: Methodsmentioning
confidence: 99%